Contribuições da ludicidade na educação infantil - FERREIRA, Fabiani do Socorro Dias (2023)
This paper discusses the importance of playfulness in Early Childhood Education, aiming to understand ludicity as an integral part of the human being as well as studying it from the perspective of school curriculum at this level of education, especially problematizing the educational process with the children who attend kindergarten classes. For this, the approach study qualitative, under a methodological path that involved bibliographical research and with official documents of the municipality of Abaetetuba-PA. During the work, we used basis the ideas of authors such as Vigotsky (1988), Ariès (1986), Bacelar (2009), Carvalho et al. (2015), Castro (2016), Brazil (2009) among others. As a result, even though incipient, we can say that children are playful, playful, dynamic and eager beings for learning with joy and pleasure, so the recreational activities at school need to start from experiences, knowledge and groupings of children, because with freedom such subjects reach the learning autonomy and a living school. Thus, playfulness gains its value in the development of young children (from kindergarten), after all, it is during this period that they know the school and, thus, begin their school educational process.